2021
DOI: 10.1063/5.0051675
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of a single tin-vacancy center to a photonic crystal cavity in diamond

Abstract: This paper was selected as Featured This paper was selected as Scilight ARTICLES YOU MAY BE INTERESTED INReal time THz imaging-opportunities and challenges for skin cancer detection

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…From the simulated mode volume of 128( λ n ) 3 for the fundamental TM 00 mode, we find the theoretical maximum Purcell enhancement of 77 in this device. The observed Purcell enhancement is comparable to that achieved in the first integrations of the diamond silicon vacancy 8,35 and tin vacancy 12,13 into photonic crystal nanobeam cavities, despite the much stronger mode confinement of those devices. We attribute this to the optimal dipole overlap of the V Si with the cavity TM mode and the less stringent emitter positioning requirements of the microdisks.…”
supporting
confidence: 63%
“…From the simulated mode volume of 128( λ n ) 3 for the fundamental TM 00 mode, we find the theoretical maximum Purcell enhancement of 77 in this device. The observed Purcell enhancement is comparable to that achieved in the first integrations of the diamond silicon vacancy 8,35 and tin vacancy 12,13 into photonic crystal nanobeam cavities, despite the much stronger mode confinement of those devices. We attribute this to the optimal dipole overlap of the V Si with the cavity TM mode and the less stringent emitter positioning requirements of the microdisks.…”
supporting
confidence: 63%
“…Although temperature increase in the device is only a few Kelvin, the requirement of constant heating can possibly be difficult in cryogenic conditions. Moving forward, the tuning method can be replaced by other methods that are compatible with cryogenics and quantum experiments, such as oxidation tuning [39,40], light-induced chemical etching [41] or laser-induced gas desorption [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we probe the spin coherence of a charge stabilised SnV − centre and find a spin lifetime T 1 >20 ms and a spin dephasing time of T * 2 = 5(1) µs at a temperature of 1.7 K. As an outlook for further applications, we implement a single shot readout scheme which yields a readout fidelity of 74 %, demonstrating the highly cycling spin conserving transitions even in the case of a large angle of 54.7°between magnetic field and the symmetry axis of the defect. It is straightforward to increase the readout fidelity by implementing means to improve the total collection efficiency of our optical setup such as utilising optical antennas [31], micropillars [3], solid immersion lenses, or photonic crystal structures [32,33]. In summary, we have shown that the charge stabilisation protocol developed in this work renders the SnV − centre suitable for reliable application in QIP, in which well defined charge states, longterm stable optical resonances for the emission of highly indistinguishable photons, long spin coherence times and efficient state readout are absolutely crucial.…”
Section: Discussionmentioning
confidence: 99%